Petroleum development contracts with multinational oil corporations : focus on the Nigerian oil industry - Gidado, Maxwell Michael (1992)
Today, the Nigerian oil industry is dominated by MNOCs who provide the technology and managerial expertise for the running of the industry. Petroleum development is a capital-intensive business involving enormous sums of money in foreign exchange. It also involves a lot of negotiations between the MNOCs and Nigeria. These negotiations often end with signing of contractual obligations by both sides. Nigeria, being a Third world country is at obvious disadvantage compared to the MNOCs in terms of risk capital, technology and management skills. The major focus of the study is on the structure and forms of petroleum development contracts between Nigeria and the MNOCs. The scope covers contracts spanning the period when oil exploration first began in Nigeria to the present. Crucial issues such as ownership, control, transfer of technology, financial returns and 'indigenisation' of the industry under the contracts is examined against the background of the country's overall foreign investment policies, petroleum policies and changes in the global oil scene. The aim is to see whether the contracts strike a balance between foreign exploitation and national policy objectives. With contemporary study of law gradually moving towards the study of law as an interdisciplinary subject, the study significantly draws on political economy writings in economics, politics and law. It is found that three kinds of petroleum contracts are operating in Nigeria. These include - concession regimes, joint venture/participation agreements and production sharing/risk service contracts. Also that the structures of these contracts are largely based on the bargaining strength of the two parties. Although, the study argued that Nigeria had improved her bargaining position through her experience over the years and membership of OPEC, yet the study demonstrates that these contracts do not allow Nigeria enough opportunity to reduce her dependence on the MNOCs. In all, the study demonstrates how difficult it is for a less developed country such as Nigeria to gain complete control over its petroleum resource (even if it has the capital) if it lacks technological and managerial capabilities. It also demonstrates the role and limitations of law in fashioning the framework for relations between MNCs and the TWCs.